Antibacterial mechanism with consequent cytotoxicity of different reinforcements in biodegradable magnesium and zinc alloys : A review - Shahed, Chowdhury Ahmed; Faiz, Ahmad; Günister, Ebru; Farhana, Mohd Foudzi; Ali, Saad; Malik, Khurshid; Wan Sharuzi, Wan Harun (KeAi Communications Co., 2023)
Benefits achieved by the biodegradable magnesium (Mg) and zinc (Zn) implants could be suppressed due to the invasion of infectious microbial, common bacteria, and fungi. Postoperative medications and the antibacterial properties of pure Mg and Zn are insufficient against biofilm and antibiotic-resistant bacteria, bringing osteomyelitis, necrosis, and even death. This study evaluates the antibacterial performance of biodegradable Mg and Zn alloys of different reinforcements, including silver (Ag), copper (Cu), lithium (Li), and gallium (Ga). Copper ions (Cu2+) can eradicate biofilms and antibiotic-resistant bacteria by extracting electrons from the cellular structure. Silver ion (Ag+) kills bacteria by creating bonds with the thiol group. Gallium ion (Ga3+) inhibits ferric ion (Fe3+) absorption, leading to nutrient deficiency and bacterial death. Nanoparticles and reactive oxygen species (ROS) can penetrate bacteria cell walls directly, develop bonds with receptors, and damage nucleotides. Antibacterial action depends on the alkali nature of metal ions and their degradation rate, which often causes cytotoxicity in living cells. Therefore, this review emphasizes the insight into degradation rate, antibacterial mechanism, and their consequent cytotoxicity and observes the correlation between antibacterial performance and oxidation number of metal ions.